FORMATION OF STUDENTS' RELIGIOUS CHARACTER THROUGH THE HABITUATION OF INFAQ AT SMKN 2 PANGKAJENE KEPULAUAN - Ridha, Abdul Aziz (Suluh Adiluhung Publisher (SAPub), 2024)
Religious character is one of the characters that each individual needs to have, and forming a religious character is one of them done at school. This research focuses on describing how the formation of religious character is carried out by schools through the habituation of infaq. The approach taken in this research is to use a descriptive qualitative approach. The subjects in this study are the Principal, Teachers, and Students of SMKN 2 Pangkajene Kepulauan. The data in this study were obtained through interviews, observation, and documentation. Then, the data were analyzed through data reduction, data presentation, and data verification. The results in this study show that religious characters formed through the habituation of infaq include: 1. Obedience in worship, 2. Caring for others, and 3. Sincerity. The process of forming students' religious character cannot be separated from several factors, including supporting factors from parents who always give more money for infaq and teachers who always remind and motivate the importance of giving.